2017
DOI: 10.3389/fphys.2017.01015
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Sarcomere Lengths Become More Non-uniform upon Activation in Intact Whole Muscle

Abstract: The sarcomere force-length relationship has been extensively used to predict muscle force potential. The common practice is to measure the mean sarcomere length (SL) in a relaxed muscle at a single location and at a given length, and this mean SL is assumed to represent the SLs at other locations across the muscle. However, in a previous study, we found that SLs are highly non-uniform across an intact passive muscle. Moreover, SL non-uniformity increases during activation in single myofibril experiments. Myofi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 41 publications
3
40
0
Order By: Relevance
“…We also measured great SL non-uniformity in our small target muscle volumes (Fig. 3B), as previously described in myofibrillar (Johnston et al, 2016;Johnston et al, 2019;Leonard and Herzog, 2010;Telley et al, 2006) and whole-muscle preparations (Lichtwark et al, 2018;Llewellyn et al, 2008;Moo and Herzog, 2018;Moo et al, 2017a).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We also measured great SL non-uniformity in our small target muscle volumes (Fig. 3B), as previously described in myofibrillar (Johnston et al, 2016;Johnston et al, 2019;Leonard and Herzog, 2010;Telley et al, 2006) and whole-muscle preparations (Lichtwark et al, 2018;Llewellyn et al, 2008;Moo and Herzog, 2018;Moo et al, 2017a).…”
Section: Resultsmentioning
confidence: 99%
“…titin) interact to affect force production in neighbouring sarcomeres with vast SL non-uniformity, either in a single myofibril or in a fibre or a muscle, as tested here. Furthermore, the SL non-uniformity observed in a tiny region of the muscle is even greater when sarcomeres from other sites of the muscle are included, thereby further exaggerating the nonuniformity (Moo and Herzog, 2018;Moo et al, 2017a). It is currently unclear why SL non-uniformity exists across all structural levels of muscle, and how its presence affects the mechanical properties of muscles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early snap-freezing and subsequent EM studies in glycerinated fiber bundles from rabbit psoas muscle showed no major changes in the filament lengths of actin or myosin within sarcomeres under rigor, isometric contraction or relaxing conditions 46 . Using an E-shaped tendon force transducer clamped to a tibialis anterior muscle of living mice and applying SHG imaging to an electrically stimulated whole muscle in vivo, a vast increase in the sarcomere length variability was seen as a broadened SL distribution, in particular at short muscle lengths (90° ankle) over long muscle lengths (180° ankle) 47 . That very recent study focused on planar images from the top 100 µm and collecting backscattered SHG signals from whole muscle without further details on the 3D aspect of myofibrillar structure under contractile activation; however, it may provide a basis to explain our observed increase in angular disorder of myofibrils if one assumes that lateral forces resulting from different sarcomere lengths of adjacent myofibrils connected by extrasarcomeric proteins, for example desmin, would induce tilts and twists to myofibrils.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the chronic exposure to eccentric-biased exercise (i.e., sprint accelerations in athletics or football) might have induced hamstring muscles architectural changes in the moderate responders. Because sarcomere lengthening is non-uniform (Moo et al, 2016 , 2017 ) and fascicles may have a regional response (i.e., more pronounced mechanical stretch might have been applied to single sarcomeres and thus fascicles) (Franchi et al, 2017 ), increases in fascicle length might be expected as an adaptive response to eccentric exercise. Those changes in fascicle length theoretically imply the addition of sarcomeres in series (Franchi et al, 2017 ), which may had a positive effect on eccentric hamstring strength at longer muscle lengths (Brockett et al, 2001 ) and produced a protective effect on the hamstring muscles (Timmins et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%